Concentration of total protein and degree of acidity (pH) of saliva when fasting and after breakfasting - Gemella N. Illahi; Rudin Tamril; Rasmidar Samad (DiscoverSys Inc., 2016)
Background: While fasting, the mouth does not work to eat and drink so that the salivary glands become less active so saliva production decreased and there was a change in eating timewhich is relation to the mastication process that impact on changes in the degree of acidity (pH) Objectives: To determine the concentration of total protein and the degree of acidity (pH) of saliva when fasting and after breakfasting. Materials and Methods: The study was observational analytic design with longitudinal (follow up study) conducted in the Hj. Halima Dg. Sikati Dental Hospital inKandea in July 2015, the sampling method was purposive sampling. Population was 35 clinical students at the Department of Dental Public Health, Faculty of Dentistry Hasanuddin University with a total sample of 16 students who fit the criteria of the study subjects. To calculate the total protein of saliva concentration using Kyltecautoanalyzerand pH meter to measure the acidity of saliva. Data was analyzed was using SPSS version 17.0 (paired t-test, p <0.05). Results: The mean of total protein (%) while fasting by 0135% ± 0.026 and the mean total protein (%) after breakfasting at 0.179% ± 0.035, while the average degree of acidity (pH) during fasting at 7.26 ± 0:24 and the average degree of acidity (pH) after breakfasting at 7.66 ± 0.23 with p-value (0.000). Conclusions: An increase in the total protein concentration and acidity (pH) after breakfasting.